The role of women in the organizational structure in family businesses in the town of Escárcega - de Jesús Delgado Cih, Dulce María (ACACIA A.C., 2021)
Gender stereotypes are based on beliefs about the role that men and women are expected to play in society. Through qualitative research, the roles that women play in family businesses will be examined, as well as the current situation of those aspects that do not allow their professional growth. However, since there are not many studies on the subject in Mexico, the results are important given that they highlight the need to study women who drive in family businesses to determine barriers such as gender stereotypes, obtained the results by application of a survey of 23 multiple-choice questions to women and men from 23 family businesses in the town of Escárcega. 54% of the people who work in these companies are women and 46% men, this means that women hold more jobs in this type of company.